Endometrial intraepithelial carcinoma: A case report and brief review - Ram Manisha; Bharadwaj Minakshi; Yadav Rajbala (Wolters Kluwer Medknow Publications, 2008)
This case report describes the precursor lesion of uterine papillary serous carcinoma (UPSC). A 65-year-old post-menopausal female presented with prolapse and vaginal discharge and underwent a hysterectomy revealing an atrophic endometrium, highly atypical endometrial glands, the lining cells of which showed pseudostratification, hobnailing, a high nuclear to cytoplasmic ratio, and prominent nucleoli. A p53 immunoreactivity score of 8 and a MIB-1 index of 80% was obtained leading to a diagnosis of endometrial intraepithelial carcinoma (EIC). Since serous EIC is commonly associated with extra-uterine serous carcinoma, it is a uniquely aggressive precursor lesion. Molecular studies support the hypothesis that EIC is a precursor of both uterine and extra-uterine invasive serous carcinomas. This is why the treatment protocol for EIC cases is total abdominal hysterectomy (TAH), accompanied by a staging procedure. In our patient, EIC was limited to the endometrium; associated with an excellent clinical outcome.